Market Efficiency of Alternative Investments - Karol WOJTOWICZ (Communications of International Proceedings, 2020)
Market efficiency theory, introduced by E.Fama, is not only the most popular but also the most discussed theory of modern finance. According to the theory, security prices immediately and fully reflect all relevant information. The empirical research has focused primarily on financial instruments and stock exchange indices. Investors, striving to reduce risk by diversifying their portfolio, increasingly use alternative investment including commodity market instruments. From the beginning of the XXIst century, there is a relevant increase in commodity derivatives. According to the Futures Industry Association, the number of futures and options traded worldwide in 2018 amounted to over 30 billion contracts. The main aim of the article is to verify the weak form of efficiency based on the selected alternative investment. The subject of the study was the most popular commodity derivates – crude oil, gold, copper, silver, corn, cocoa, and cotton. The analysis was carried out in the years 2000-2019. Research has shown that alternative investments involving financial commodity instruments met the conditions of the weak form of market efficiency. Both the runs tests and auto-correlation tests proved random price formation. There were also no seasonal anomalies.
Keywords: Market efficiency; alternative investments; commodities.